Why Information Matters: Examining the Consequences of Suggesting That Pedophilia Is Immutable - Tozdan, Safiye (International journal of offender therapy and comparative criminology, 2018)
In this study, the impact of suggesting that pedophilia is immutable on a man’s specific self-efficacy for modifying his sexual interest in children was examined in 94 men with a sexual interest in children. The participants were selected from differing contexts and included non-forensic patients, forensic patients, and participants from the Internet. Randomly distributed to two conditions, the mutable condition group received the information that experts consider pedophilia to be modifiable, whereas the immutable condition group received the information that experts consider pedophilia to be stable. Afterward, the participants’ levels of specific self-efficacy for modifying their sexual interest in children were assessed. Non-forensic participants in the mutable condition reported higher levels of specific self-efficacy than those in the immutable condition. No differences in specific self-efficacy were revealed for the forensic and Internet participants when comparing the mutable and immutable conditions. It would appear appropriate to avoid generalized and absolute statements about the (im)mutability of sexual interest in children, as scientific research on this topic remains insufficient. Furthermore, given the present results, such statements might have serious consequences for an individual’s belief in being able to change his sexual interest in children.